Improving the intercellular uptake and osteogenic potency of calcium phosphate via nanocomplexation with the RALA peptide - Kelly, Daniel (My University, 2020)
Calcium phosphate-base materials (e.g., alpha tri-calcium phosphate (α–TCP)) have been shown to promote osteogenic differentiation of stem/progenitor cells, enhance osteoblast osteogenic activity and mediate in vivo bone tissue formation. However, variable particle size and hydrophilicity of the calcium phosphate result in an extremely low bioavailability. Therefore, an effective delivery system is required that can encapsulate the calcium phosphate, improve cellular entry and, consequently, elicit a potent osteogenic response in osteoblasts. In this study, collagenous matrix deposition and extracellular matrix mineralization of osteoblast lineage cells were assessed to investigate osteogenesis following intracellular delivery of α-TCP nanoparticles. The nanoparticles were formed via condensation with a novel, cationic 30 mer amphipathic peptide (RALA). Nanoparticles prepared at a mass ratio of 5:1 demonstrated an average particle size of 43 nm with a zeta potential of +26 mV. The average particle size and zeta potential remained stable for up to 28 days at room temperature and across a range of temperatures (4–37 °C). Cell viability decreased 24 h post-transfection following RALA/α-TCP nanoparticle treatment; however, recovery ensued by Day 7. Immunocytochemistry staining for Type I collagen up to Day 21 post-transfection with RALA/α-TCP nanoparticles (NPs) in MG-63 cells exhibited a significant enhancement in collagen expression and deposition compared to an untreated control. Furthermore, in porcine mesenchymal stem cells (pMSCs), there was enhanced mineralization compared to α–TCP alone. Taken together these data demonstrate that internalization of RALA/α-TCP NPs elicits a potent osteogenic response in both MG-63 and pMSCs.
Keywords: Immunocytochemistry; delivery system; collagenous matrix depositio; Calcium phosphate; Peptide; RALA; Intercellular; Osteogenic; Bone engineering; Immunocytochemistry; delivery system; collagenous matrix depositio